Escaping loneliness Through Airbnb host-guest interactions - Farmaki, Anna; Stergiou, Dimitrios P. (My University, 2019)
This research note explores the relationship between loneliness and the use of Airbnb from the perspective of host-guest interactions. Findings from semi-structured interviews with co-habiting Airbnb hosts and guests, identify loneliness as a key driver and an important element of the peer-to-peer accommodation experience. By offering a typology of Airbnb users in terms of their loneliness-interaction interface, findings contribute to a better compatibility between Airbnb hosts and guests who experience loneliness and social isolation. Thus, in light of the increasing rates of loneliness, this research note provide support to international attempts to ameliorate the social problem of loneliness. Considering that loneliness has been largely overlooked in tourism research, the empirical evidence offered in this research note may serve as a stepping stone for further research on loneliness within tourism studies.
Keywords: Airbnb; Host-guest interactions; Loneliness